Retour

Source de exo01.tex

Fichier TeX
Image PNG
%@Titre: Groupe Nord -- 2006
Soit $D=(2x+3)^2+(2x+3)(7x-2)$.
\begin{myenumerate}
  \item Développer et réduire $D$.
  \item Factoriser $D$.
  \item Calculer $D$ pour $x=-4$.
  \item Résoudre l'équation $(2x+3)(9x+1)=0$.
\end{myenumerate}
%@Correction:
\begin{myenumerate}
  \item\[\Eqalign{
D&=(2x+3)^2+(2x+3)(7x-2)\cr
D&=(2x)^2+2\times2x\times3+3^2+2x\times7x+2x\times(-2)+3\times7x+3\times(-2)\cr
D&=4x^2+12x+9+14x^2-4x+21x-6\cr
D&=18x^2+29x+3\cr
}\]
\item\[\Eqalign{
D&=(2x+3)^2+(2x+3)(7x-2)\cr
D&=(2x+3)(2x+3)+(2x+3)(7x-2)\cr
D&=(2x+3)\times\left[(2x+3)+(7x-2)\right]\cr
D&=(2x+3)\times\left[2x+3+7x-2\right]\cr
D&=(2x+3)\times(9x+1)\cr
}\]
\item $D=18\times(-4)^2+29\times(-4)+3=18\times16-116+3=288-116+3=175$
\item C'est un produit nul donc
\[\Eqalign{
2x+3&=0&&\mbox{ou}&&9x+1&=0\cr
2x&=-3&&&&9x&=-1\cr
x&=\frac{-3}2&&&&x&=\frac{-1}9\cr
}\]
Les solutions de l'équation sont $x=-\dfrac13$ et $x=-\dfrac19$.
\end{myenumerate}